1999
DOI: 10.1366/0003702991947612
|View full text |Cite
|
Sign up to set email alerts
|

New Procedure for Quantitative Elemental Analysis by Laser-Induced Plasma Spectroscopy

Abstract: A new procedure, based on the laser-induced plasma spectroscopy (LIPS) technique, is proposed for calibration-free quantitative elemental analysis of materials. The method here presented, based on an algorithm developed and patented by IFAM-CNR, allows the matrix effects to be overcome, yielding precise and accurate quantitative results on elemental composition of materials without use of calibration curves. Some applications of the method are illustrated, for quantitative analysis of the composition of metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
405
0
17

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 782 publications
(424 citation statements)
references
References 29 publications
2
405
0
17
Order By: Relevance
“…For instance, it has been demonstrated that the analysis of 9 elements in an aluminum alloy can be carried out by employing the spectral line intensities detected from all constituents of the sample over a wide spectral wavelength range and plotting a family of Boltzmann curves. 40 An improved procedure was developed to account for line self absorption (a effect that induces non-linearity to the analytical curve) and applied to the analysis of steel, with even more success. 41 Research in the field of calibration-free LIBS will certainly continue to grow and it represents a very interesting aspect of the technique with respect to overcoming one of its drawbacks related to severe matrix effects the characteristics of the sample can impose on the emission spectra.…”
Section: Theoretical Studies and Calibration-free Libsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been demonstrated that the analysis of 9 elements in an aluminum alloy can be carried out by employing the spectral line intensities detected from all constituents of the sample over a wide spectral wavelength range and plotting a family of Boltzmann curves. 40 An improved procedure was developed to account for line self absorption (a effect that induces non-linearity to the analytical curve) and applied to the analysis of steel, with even more success. 41 Research in the field of calibration-free LIBS will certainly continue to grow and it represents a very interesting aspect of the technique with respect to overcoming one of its drawbacks related to severe matrix effects the characteristics of the sample can impose on the emission spectra.…”
Section: Theoretical Studies and Calibration-free Libsmentioning
confidence: 99%
“…The calibration-free method was used for spectra analyses. 40 The use of this method allowed the quantification of the concentrations of all alloy elements (major and trace elements), even when present in concentrations below the usual LIBS detection limits. Values near to the nominal concentrations were encountered with errors lower than 1% and RSD about 0.1%.…”
Section: Alloys and Metallurgic Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of beryllium and tungsten were determined quantitatively for the Be-W sample in figure 3b using the calibration-free LIBS (CF-LIBS) method [5]. CF-LIBS relies on determining the temperature of the plasma from a Saha-Boltzmann plot [6] drawn for each emitting species in the plasma plume.…”
Section: Quantitative Studies By Calibration-free Libsmentioning
confidence: 99%
“…The procedure of CF-LIBS has been described in detail by Ciucci et al [18]; therefore, we only introduce the basic characteristics of this method for better depicting the procedure of IRSAC. Assuming the plasma is optically thin and in local thermodynamic equilibrium (LTE) in the temporal window of signal acquisition, the measured integral line intensity can be expressed as:…”
Section: Calibration-free Libsmentioning
confidence: 99%